Public debt requirements in a regime of price stability - Carl Christian von Weizsäcker (Max Planck Institute for Research on Collective Goods, 2011)
The logic of this paper is based on a modernisation of Austrian capital theory as applied to a closed economy growing in a steady state. Here the philosophy is this: capital is time embodied in produced goods. In steady states, this philosophy works well as an aggregation device for an arbitrary number of distinct produced goods. The basic theorem of this approach (Section VII) is this: in a capital market equilibrium without public debt and hence in a general equilibrium without public debt the average period of production equals the average waiting period of households. Calibration of the parameters of the production sector and the consumption sector then leads to the result that the equilibrium risk free real rate of interest (Wicksell's natural rate of interest) is negative for the OECD+China area. What distinguishes the twenty-first century from earlier times is the high life expectancy of people and the ensuing extensive average pension period. These characteristics are responsible for the high average waiting period. Only with a negative real rate of interest can the average period of production catch up with the high average waiting period. Under price stability the risk free real rate of interest cannot become negative. Public debt causes the equilibrium risk free rate of interest to rise: the public debt period () plus the average period of production (DT) equal the average waiting period (Z). Thus substantial public debt is required for the goal of price stability. We thus come to a different view of public debt: it is inconsistent with the goal of a zero public debt. This different view of public debt (even apart from Keynesian considerations) has been introduced by Samuelson already in the year 1958. My Austrian capital theoretic approach allows me to show that it is the relevant view for the 21 st century.
Keywords: 330; Steady-State-Wachstum; Kapitaltheorie; Österreichische Schule; Öffentliche Schulden; Preisniveaustabilität; Realzins; Theorie